BUDAYA NASIONAL DAN RISIKO FRAUD - Nia Amalia; Rr. Sri Handayani (Jurnal Reviu Akuntansi dan Keuangan, 2019)
This study aims to obtain empirical evidence about the influence of national culture on fraud risk. The lack of literature that discusses fraud risk makes researchers interested in researching the relevance of national culture to understanding the risk of fraud so that it can help reduce fraud. Six dimensions of Hofstede's national culture were used in this study. As well, the Corruption Perception Index is proxied to measure fraud risk.The population in this study are countries in the world registered with the Corruption Perceptions Index 2018 by the Transparency International organization. The sample selection used a purposive sampling method and selected 81 sample countries. Multiple linear regression analysis was used as an analytical tool in this study.The results of the analysis of this study reveal that the dimension of power distance has a positive and significant effect on the risk of fraud. The dimensions of individualism, long-term orientation and indulgence negatively and significantly affect the risk of fraud. On the other hand the dimensions of uncertainty avoidance and masculinity have a positive but not significant effect on risk to the risk of fraud.